Biodiesel investment in a disruptive tax-credit policy environment. (December 2018) - Liu, Shen; Colson, Gregory; Wetzstein, Michael
Abstract: An investigation of Poisson type policy jumps on biodiesel investment considers the theory of investment under uncertainty. The analysis studies the probability of implementing a policy if it is not in effect and the probability of withdrawal if it is in effect. An application models the policy-switching regime of the discontinuous U.S. federal tax credit of $1.00 per gallon on biodiesel. Results support that time inconsistent government policies do lead to market uncertainty. The analysis reveals a pronounced negative impact on decisions to invest in a biodiesel refinery. Results do indicate a consistent policy-switching regime may not be that disruptive to the emerging biodiesel industry. It is policy uncertainty that drives the option-pricing thresholds and a consistent policy switching does not increase the uncertainty. Highlights: Considers transience in government energy policy. It is important to make a distinction between policy uncertainty and known policy switching. A long-run energy policy can result in a smooth development of a renewable energy industry.